Residues of antibiotics in yeasts from ethanol production: a possible contamination route for feedingstuffs. Issue 4 (3rd April 2021) - Hoff, Rodrigo Barcellos; Molognoni, Luciano; Deolindo, Carolina Turnes Pasini; de Oliveira, Thais; Mattos, Joana Letícia Sardá; Oliveira, Luan Valdemiro Alves de; Daguer, Heitor
Abstract: Sugarcane yeast and brewer's yeast from ethanol production are widely used as ingredients of animal feed formulations in Brazil. To avoid the contamination of the must in ethanol production refineries, the use of antibiotics is one of the main preventive treatments. Thus, there is a risk of antibiotic residues carry over from yeast to animal feed. This unintentional addition of antibiotics can produce non-compliant feed products, due to regulatory aspects and their toxicity for animals. The results of an exploratory program to assess the occurrence of over 60 antibiotics and other pharmaceuticals in 27 sugarcane yeast and brewer's yeast samples were described. Monensin was present in seven samples with concentrations ranging from 0.47 to 263.5 mg kg −1 . Other antibiotics quantitated were virginiamycin (2.25 mg kg −1 ) and amprolium (0.25 mg kg −1 ). Monensin in sugarcane yeast may represent a risk for further feeds production, especially for those products intended for sensible species such as equines and rabbits, for which monensin has toxic effects.